Effects of Outcome Information on Evaluations of Managerial Decisions - Brown, Clifton E.; Solomon, Ira (The Accounting Review, 1987)
[This paper examines the effects of outcome information on managerial decision evaluations. Specifically, based on cognitive considerations, hypotheses are developed about a base-line effect of outcome information and attenuation of that effect by: (1) the evaluator's prior involvement with the evaluatee's decision process, and (2) the extent to which reported outcomes imply evaluatee responsibility for anticipating such outcomes. The hypotheses are confirmed by the results of an experiment set within the context of capital budgeting. Implications of these results are discussed in terms of information system design and the process of generalizing psychological research into accounting contexts.]